An inverse design tool for two‐dimensional blade generation in aerospace engineering education. Issue 2 (19th November 2018) - Zhu, Chengxiang; Li, Mingfeng; Shi, Chongguang; You, Yancheng
Abstract: An inverse design tool based on the theory of characteristic lines and coordinate system transformation, showing the capability of generating two‐dimensional blades with a given pressure distribution along the surface, has been coded with MATLAB and developed in the present work for undergraduate students in aerospace engineering. Validations of the inverse design tool have been evaluated for both single blade surface and plane cascade which show good agreements as comparing to the computational fluid dynamics (CFD) results. This tool provides an intuitive impression on blade generation and a clear picture for the underlying principles of blade design for undergraduate students in the major of aerospace engineering, which also serves sufficient freedom for students to derive their own blade geometry by merely prescribing a surface pressure distribution.